Influencia del Branding interno en la orientación de los colaboradores hacia la experiencia del cliente en hoteles de Barranquilla (2021)
This research aims to analyze the influence of internal branding on employee orientation towards customer experience in hotels in Barranquilla. The study was carried out from a quantitative approach, from descriptive and correlational research, non-experimental, and transectional design, whose sample consisted of 55 employees who belong to 5 member hotels of the Asociación Hotelera y Turística de Colombia [Cotelco], Chapter Atlántico. Additionally, the study considered the administrators or managers of the participating hotels to complement some results. A survey was used to collect the information. It consisted of 35 Likert-type scale items. The collected data were processed through descriptive statistics and multiple linear regression analysis to determine the correlation between the variables. The results showed that the dimensions of internal branding (brand-centered human resource management, internal brand communications, and brand leadership) are present in the organizational dynamics of the participating hotels. Likewise, employees showed significant results in the components of emotional intelligence, cultural intelligence and hospitality experiential intelligence, which confirms that they are oriented towards the customer experience. Finally, it was established that there is a weak positive correlation between internal branding and the orientation of employees towards customer experience, where brand leadership was shown to be the most influential dimension.